Grebeg Suro di Bumi Reog Sebagai Destinasi Wisata yang Berkemajuan - Atiek Rohmiyati; Rachmawaty (STIE Pariwisata API Yogyakarta, 2023)
Ponorogo, which is known as Bumi Reog, have a tradition of Grebeg Suro to commemorate the night of 1 Suro or 1 Muharram in Islamic lunar year. The event holds for a full month and filled with various cultural arts performances and National Reog Festivals. It was a local wisdom turned into a progressive national and even international tourism destination. The purpose of the research is to inspire other regions to develop their own local wisdom into tourism object for economic and socio-cultural prospects. The research used anthropology tourism method with diachronic approach. The data gathered was analyzed using data triangulation technique to gain a more comprehensive understanding of a situation. The research result showed that a creative commodification on local wisdom could improve the local economy. It could be concluded that Grebeg Suro of Ponorogo, which has its roots in local wisdom, has a significant impact on the community and local economy. Among the key factor behind the successful event is its distinctive fashion. It is recommended that the event should also promote Panaragan signature batik with reog and peacock motifs and to promote culinary places that serve Ponorogo specialty foods such as sate, gule, pecel and dawet jabung.